Effect of microenvironment on the fluorescence of 2-hydroxy-substituted Nile Red dye: A new fluorescent probe for the study of micelles - GÖKTÜRK, SİNEM (My University, 2003)
Absorption spectra and fluorescence properties of 2-hydroxy-substituted Nile Red (HONR) have been studied in various solvents and micelles. The solvent dependence of the rate constant of the internal conversion was found to exhibit two entirely distinct domains. Going from apolar toward polar solvents, first, the deceleration of the radiationless deactivation was observed due to the diminishing extent of the vibronic coupling between the neighboring S1 and S2 singlet excited states. After reaching a minimum, the rate of the transition to the ground state significantly increased in alcohols because of the efficient energy dissipation via intermolecular hydrogen bonding. The correlations of the excited-state energy, fluorescence lifetime, absorption, and fluorescence maxima with the ET(30) solvent polarity parameter were used to characterize the local environment of HONR in micelles. Fluorescence quenching studies provided further evidences for the differences in the binding site of the dye in cationic, anionic and nonionic micelles.